Theoretical Study of Transition Metal Oxide Clusters ($TM_nO_m$) [(TM-Pd, Rh, Ru) and ($n, m =1, 2)$] (Journal of Atomic and Molecular Sciences, 2012)
Structural, vibrational and electronic properties of the transition metal oxide clusters (PdO, RhO, and RuO) are calculated to investigate the changes, when an electron is either added or removed from the corresponding neutral clusters by Density functional theory with the B3LYP exchange-correlation functional using LANL2DZ as the basis set. In the first place, geometrical optimization of the nanoclusters have been carried out. In the next step, these optimized geometries are used to calculate the binding energy and HOMO-LUMO gap (band gap) of the clusters. The calculated results tell that the addition of an electron to the neutral clusters induces appreciable structural changes relative to the case when an electron is removed. The changes in vibrational properties can be explained in terms of the variation of the interatomic distances upon removing or adding the electron.
Keywords: transition metaloxide; structure; stability; DFT.